Extrusion and meniscal mobility evaluation in case of ramp lesion injury: a biomechanical feasibility study by 7T magnetic resonance imaging and digital volume correlation - Severyns, M.; Zot, F.; Harika-Germaneau, G.; Germaneau, A.; Herpe, G.; Naudin, M.; Valle, V.; Danion, J.; Vendeuvre, T. (Frontiers in Bioengineering and Biotechnology, 2024)
The existing body of literature on the biomechanical implications of ramp lesions is limited, leaving a significant gap in our understanding of how these lesions impact joint kinematics and loading in the medial compartment. This cadaveric biomechanical study aims to address this gap by employing an innovative Digital Volume Correlation (DVC) method, utilizing 7 Tesla Magnetic Resonance Imaging (MRI) images under various loading conditions. The primary objective is to conduct a comprehensive comparison of medial meniscal mobility between native knees and knees affected by grade 4 ramp lesions. By focusing on the intricate dynamics of meniscal mobility and extrusion, this work seeks to contribute valuable insights into the biomechanical consequences of medial meniscus ramp lesions.Methods. An initial set of 7T MRI imaging sessions was conducted on two intact native knees, applying load values up to 1500N. Subsequently, a second series of images was captured on these identical knees, with the same loads applied, following the creation through arthroscopy of medial meniscus ramp lesions. The application of DVC enabled the precise determination of the three components of displacement and spatial variations in the medial menisci, both with and without ramp lesions.indicate that, following the application of axial compression load, menisci exhibit increased extrusion and posterior mobility as observed through DVC.Discussion. Injuries associated with Subtype 4 medial meniscus ramp lesions appear to elevate meniscal extrusion and posterior mobility during axial compression in the anterior cruciate ligament of intact knees. Following these preliminary results, we plan to expand our experimental approach to encompass individuals undergoing weight-bearing MRI. This expansion aims to identify meniscocapsular and/or meniscotibial insufficiency or rupture in patients, enabling us to proactively reduce the risk of osteoarthritic progression.